The Probability of Socioeconomic Status and Demographics Effect on Birth Weight Babies (Journal of Family Sciences, 2023)
Low Birth Weight (LBW) can lead to stunting and the impact of stunting in long term. Socioeconomic status and demographic factors can be a cause of baby’s low birth weight. The study aims to analyze the probability of a household giving birth to a baby with low birth weight. The data used in the research uses data from the 2021 National Socio-economic Survey (Susenas). The model used in this study is a logit model with a total of 2,203,472. The result shows poor households, household partners with low education, and household members who smoke have a significantly lower probability of giving birth to normal baby’s weight Meanwhile, households who work in the formal sector and live in urban areas have a significantly higher probability of giving birth to normal-weight babies. Households with a good socioeconomic status will provide optimal nutrition. Households in urban areas still have a better level of health than those in rural areas and households that do not smoke will give birth to healthier babies with normal weight.